Hubungan Komunikasi Efektif Guru dengan Perilaku Bullying Siswa Kelas X dan XI SMK Mutiara 17 Agustus Kota Bekasi Tahun 2023 - Angga Prayuda; Nurti Y. K. Gea; Riris Ocktryna (Jurnal Medicare, 2024)
Background: Bullying is a serious issue in many countries, including Indonesia. KPAI data shows that bullying has dominated cases of violence in education from 2011 to 2019. Bullying is an aggressive, intentional, and repetitive act that involves a power imbalance and impacts various aspects of life. Research Objective: To examine the relationship between effective teacher communication and bullying behavior among students at SMK Mutiara 17 Agustus Bekasi, grades X and XI, in 2023. Research Method: Quantitative research with an Observational Analytic design and a Cross-Sectional approach. Results: The Chi-Square test showed a p value of 0.003 < α (0.05), indicating that Ha is accepted. Conclusion: There is a relationship between effective teacher communication and bullying behavior among grade X and XI students at SMK Mutiara 17 Agustus Bekasi in 2023.